Attitude Assessment Analysis on the 2013 Curriculum Based on the Implementation of Rehearsal Pairs Practice (PRP) Model - Khudaefah Khudaefah; Widinda Normalia Arlianty (Universitas Islam Indonesia, 2020)
The purpose of this study was to know the assessment of student attitudes in the 2013 curriculum after being applied to learning with the Rehearsal Pairs Practice model (PRP). This research was conducted at Senior high school (Madrasah Aliyah) Sunan Pandanaran Yogyakarta. The application of this learning model is carried out on the buffer solution material. The population of this research is all students of class XI MA Sunan Pandanaran academic year 2017/2018. The sample in this study amounted to two classes taken by purposive sampling technique. The data collection technique was performed using a non-test technique, namely using a questionnaire. Data analysis was performed using the Independent Sample T-Test Statistical Test. The results obtained are no differences in student achievement in attitude after being applied with the Practice Rehearsal Pairs (PRP) model.